”Att befrias fran varje horisontlinje”. Birgitta Lillpers poetiska landskap - Niewiarowska-Rasmussen, Ewa (Folia Scandinavica Posnaniensia, 2007)
The paper constitutes an analysis of the poetry of Birgitta Lillpers in the context of the postmodern break-up of traditional definitions of literary genres. The characteristic features of the Swedish poet's work are ambiguity, fragmentation, and a diffuse persona of the speaker. Lillpers' poetry is rich in lexical, semantic and syntactic experimentation.